2019
DOI: 10.1159/000499645
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Solute Clearance, Hospitalization Rate, and Aortic Arch Calcification between Online Hemodiafiltration and High-Flux Hemodialysis: A 6-Year Observational Study

Abstract: Background/Aims: Studies on the long-term clinical benefits of hemodiafiltration (HDF) and high-flux hemodialysis (HFHD) are very limited. This study aimed to investigate the hospitalization rate and aortic arch calcification (AAC) of these two dialysis modalities over 6 years. Methods: Participants who received regular HDF and HFHD in one hospital-facilitated hemodialysis center were prospectively enrolled after matching for age, sex, and diabetes between January 2009 and December 2014. Medical records were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…On the other hand there was no significant difference between both groups as regard serum creatinine, sodium and potassium levels, which agrees with Hao et al (12) , who showed no significant difference between high flux dialysis and online HDF after 6 years.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand there was no significant difference between both groups as regard serum creatinine, sodium and potassium levels, which agrees with Hao et al (12) , who showed no significant difference between high flux dialysis and online HDF after 6 years.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas most randomized controlled trials to date have mainly concentrated on the comparison between HFHD and HDF, or HFHD and LFHD in relation to the clearance of β2M in HD patients, there have been few related to combined HFHD and HDF therapy. In a 6‐year observational study, hospitalization rates and aortic arch calcification were equal between HDF and HFHD 15 . Several recent studies on HFHD combined with HDF have focused on the association between different dialysis models and phosphorus removal 16 or serum calcification propensity 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In a 6-year observational study, hospitalization rates and aortic arch calcification were equal between HDF and HFHD. 15 Several recent studies on HFHD combined with HDF have focused on the association between different dialysis models and phosphorus removal 16 or serum calcification propensity. 17 In another study, patients were switched from HFHD to HDF therapy, which did not result in significant changes in hsCRP, β2M, or ESA doses.…”
Section: Introductionmentioning
confidence: 99%